Anti-inflammation biomaterial platforms for chronic wound healing. (20th May 2021) - Xu, Zejun; Liang, Biao; Tian, Junzhang; Wu, Jun
Abstract : Chronic wound has developed into one of the most serious health problems worldwide; the rate-limiting stage of chronic wound healing is the inflammation stage; we reviewed the advances and impact of various anti-inflammatory biomaterial platforms. Abstract : Nowadays, there has been an increase in the number of people with chronic wounds, which has resulted in serious health problems worldwide. The rate-limiting stage of chronic wound healing has been found to be the inflammation stage, and strategies for shortening the prolonged inflammatory response have proven to be effective for increasing the healing rate. Recently, various anti-inflammatory strategies (such as anti-inflammatory drugs, antioxidant, NO regulation, antibacterial, immune regulation and angiogenesis) have attracted attention as potential therapeutic pathways. Moreover, various biomaterial platforms based on anti-inflammation therapy strategies have also emerged in the spotlight as potential therapies to accelerate the repair of chronic wounds. In this review, we systematically investigated the advances of various biomaterial platforms based on anti-inflammation strategies for chronic wound healing, to provide valuable guidance for future breakthroughs in chronic wound treatment.